Current problems in education - Tutor Nishanova Nigora Alisherovna (Periodica Journal, 2025)
The upbringing of the young generation is one of the main tasks of society: it is an important basis for the upbringing of our youth into enlightened, mentally and physically healthy, loyal national and universal values, educated and enterprising young people, patriotic, hardworking and virtuous people.
Keywords: Abu Ali ibn Sina; Grandmaster Amir Temur; Alisher Navoi